Biological Fixation of Sloping Land Using Sulla Crop, El Rhahla – Siliana, Northwestern Tunisia - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
Biological Fixation of Sloping Land Using Sulla Crop, El Rhahla – Siliana, Northwestern Tunisia.